2017
DOI: 10.1371/journal.ppat.1006532
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica serovar-specific transcriptional reprogramming of infected cells

Abstract: Despite their high degree of genomic similarity, different Salmonella enterica serovars are often associated with very different clinical presentations. In humans, for example, the typhoidal S. enterica serovar Typhi causes typhoid fever, a life-threatening systemic disease. In contrast, the non-typhoidal S. enterica serovar Typhimurium causes self-limiting gastroenteritis. The molecular bases for these different clinical presentations are incompletely understood. The ability to re-program gene expression in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 50 publications
2
29
0
Order By: Relevance
“…4c). A previous report indicated that S. Typhimurium infection results in STAT3 phosphorylation in HeLa and Henle epithelial cells but did not identify the causative effector (Hannemann and Galan, 2017). We confirmed S .…”
Section: Resultsmentioning
confidence: 99%
“…4c). A previous report indicated that S. Typhimurium infection results in STAT3 phosphorylation in HeLa and Henle epithelial cells but did not identify the causative effector (Hannemann and Galan, 2017). We confirmed S .…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, although there is a bias towards discussing the pseudogenisation and absence of T3SS effectors in S. Typhi, computational or experimental screens to identify novel effectors have, to our knowledge, not been performed with S. Typhi. However, based on homology to T3SS effectors from other bacterial pathogens, putative S. Typhi-specific effectors have been identified, including STY1076 (NleG family), STY1423 (EspN), and STY1360 (OspB) (Hannemann & Galán, 2017). Of these, STY1076 (t1865) can be secreted in a SPI-1 and SPI-2 T3SS-dependent manner, and translocated into host cells, although a functional role during S. Typhi infection has not yet been described (manuscript in preparation).…”
Section: Gogamentioning
confidence: 99%
“…However, based on homology to T3SS effectors from other bacterial pathogens, putative S. Typhi-specific effectors have been identified, including STY1076 (NleG family), STY1423 (EspN), and STY1360 (OspB)(Hannemann & Galán, 2017). These results suggest that SptP is nonfunctional in S. Typhi, which may have wider ramifications when considering additional effectors with varying sequence identities between S. Typhi and S. Typhimurium.…”
mentioning
confidence: 99%
“…S. Typhimurium can directly benefit from hyperaccuracy of translation through accurate protein production and proteome integrity and indirectly through proper activation of the stringent response during adverse growth conditions. S. Typhimurium can use these translational stress responses to complement the well-characterized transcriptional responses that are the foundation for S. Typhimurium pathogenesis to maintain resiliency during oxidative stress and survive within the host microbiome (30)(31)(32).…”
Section: Proofreading Protects Cells From Mistranslation Under Adversementioning
confidence: 99%